2018
DOI: 10.3389/fimmu.2018.00542
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Pemphigoid Triggered by Thermal Burn Under Medication With a Dipeptidyl Peptidase-IV Inhibitor: A Case Report and Review of the Literature

Abstract: Bullous pemphigoid (BP) is a common autoimmune blistering disease in which autoantibodies mainly target the hemidesmosomal component BP180 (also known as type XVII collagen) in basal keratinocytes. Various triggering factors are known to induce BP onset, including radiotherapy, burns, ultraviolet exposure, surgery, and the use of dipeptidyl peptidase-IV inhibitors (DPP4i), which are widely used antihyperglycemic drugs. Here, we present a case of BP triggered by a thermal burn under medication with DPP4i. A 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 66 publications
(37 reference statements)
2
37
0
Order By: Relevance
“…1,2 Its location in the hand is infrequent (only six cases described so far), but unlike other locations, where it is usually an incidental histological finding, PD of the palm typically presents as hyperpigmented macules. [1][2][3] We present four additional cases corroborating that this entity has a well-defined clinical-dermoscopic pattern. Four women aged 25, 28, 39 and 64 years were assessed.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…1,2 Its location in the hand is infrequent (only six cases described so far), but unlike other locations, where it is usually an incidental histological finding, PD of the palm typically presents as hyperpigmented macules. [1][2][3] We present four additional cases corroborating that this entity has a well-defined clinical-dermoscopic pattern. Four women aged 25, 28, 39 and 64 years were assessed.…”
supporting
confidence: 67%
“…To date, there have been several reports focusing on the prodrome of BP. [1][2][3] The precipitating factors of BP are ultraviolet light, radiation therapy, thermal burn, surgical wounds, surgical grafts, ostomy and several traumatic triggers (Koebner phenomenon). 4 In addition, BP is occasionally preceded by non-specific lesions such as erythema multiforme and urticarial or eczematous rash with weeks' or months' duration.…”
Section: Bullous Pemphigoid Developed On Nummular Eczema Lesionsmentioning
confidence: 99%
“…As for diagnosis, we examined DIF results of 229 DIBP patients discussed in two retrospective case-control studies and in 42 case reports, and found 186 DIF positive patients, 15 DIF negative, and 28 with an unclear DIF result. Although in the literature some reviews and retrospective case-control studies do not always report DIF results, in the vast majority of DIBP patients, the diagnosis was obtained through the gold standard approach: DIF [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Trigger Factorsmentioning
confidence: 99%
“…Another autoimmune skin blistering disorder that is pathogenetically often connected to malignancy or RT is bullous pemphigoid (BP). The so far published cases comprise similarly to RT-associated pemphigus more than 30 (42), including a stage IV melanoma patient with dual exposure to PD-1 checkpoint inhibition and RT therapy (43). Nguyen et al have summarized 29 patients with BP following radiation for malignancy treatment.…”
Section: Discussionmentioning
confidence: 99%